(untitled) (Bangladesh Journal of Botany, 2024)
Experiment was designed to screen out lentil genotypes against Stemphylium blight (SB). Thirty-five test genotypes along with one moderately susceptible popular local control ‘Moitree’ were grown under natural epiphytotic condition in the farm of BCKV during 2020-21 and 2021-22. Genotypes wise crop phenological characters, yield and disease severity data were recorded. The result revealed, genotypes ILL10838/ILWL11/X2016S was resistant to SB with highest yield (1184.00 kg/ha) followed by 8114/10956/16-1 (1112.20 kg/ha) and IPL 220 (1072.90 kg/ha) with MR reaction. Pooled analysis of two years experimental data used to develop the model Y = 336.21 + 6.12x [R2 = 0.86] explained that there is an increase of yield 6.12 kg/ha with every 1 unit increase in the number of pods per plant. Correlation of determination value (R2 = 0.86) proved the feasibility of the model. Lentil genotypes ILL10838/ ILWL11/X2016S and 8114/10956/16-1 are the best suited for its cultivation and may scaled up for future breeding programme. Bangladesh J. Bot. 53(2): 381-389, 2024 (June)